한·칠레 FTA협정 발효 이후 우리나라의 농산물 교역 동향과 시사점 - 임정빈 (경상대학교, 2005)
ABSTRACT This study analyses the trends of agricultural trade between Korea and Chile after the effectuation of bilateral FTA, and seeks to the policy implication on the future FTA agreements with other countries. The value of trade between Korea and Chile is increased after the launch of FTA. As our expectation, the export of Korean manufactured goods such as automobiles, wireless phone, TV and video camera has sharply been increased through the effects of tariff elimination whereas the import of Chilean agricultural products such as wine, pork, kiwi, and fruit preparation has been increased. However the import of Chilean fresh fruit such as grape and peach has not been greatly increased rather than prior expectation. It is mainly because of seasonal tariff measure for grape and plant quarantine for peach and other fruits. Particularly the negative impacts on the Korean fruit industry of FTA with Chile will be shown in the mid-term (3～10years) according to the effects of extinguishing quarantine measure. Therefore this paper overviews the process of mid-term effects of Korea-Chiles FTA on agricultural sector and presents the Korean FTA strategies in order to minimize the negative impacts on agricultural sector.
Keywords: 자유무역협정; 시장개방; 농산물 무역; 칠레; 관세철폐; Free Trade Agreement; Market Liberalization; Agricultural Trade; Chile; Tariff Elimination